2006
DOI: 10.5194/npg-13-185-2006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stability on the flux-profile relationships for wind speed, <i>Φ</i><sub>m</sub>, and temperature, <i>Φ</i><sub>h</sub>, for the stable atmospheric boundary layer

Abstract: Abstract. Data from SABLES98 experimental campaign have been used in order to study the influence of stability (from weak to strong stratification) on the flux-profile relationships for momentum, φ m , and heat, φ h . Measurements from 14 thermocouples and 3 sonic anemometers at three levels (5.8, 13.5 and 32 m) for the period from 10 to 28 September 1998 were analysed using the framework of the local-scaling approach (Nieuwstadt, 1984a;1984b), which can be interpreted as an extension of the Monin-Obukhov simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 63 publications
11
55
0
Order By: Relevance
“…However, with strongly stratified flow, the vertical mixing of scalars by the turbulence may become extremely weak e.g., [25] while the horizontal transport by submeso motions can be rather large, as found in this study. The vertical flux by the submeso motions is difficult to estimate due to large sampling errors and difficulties measuring very weak vertical motions, and is outside the scope of this study.…”
mentioning
confidence: 60%
“…However, with strongly stratified flow, the vertical mixing of scalars by the turbulence may become extremely weak e.g., [25] while the horizontal transport by submeso motions can be rather large, as found in this study. The vertical flux by the submeso motions is difficult to estimate due to large sampling errors and difficulties measuring very weak vertical motions, and is outside the scope of this study.…”
mentioning
confidence: 60%
“…Wyngaard and Coté (1971) named this detached turbulence as z-less stratification. Previous studies reported that turbulence structure showed the properties of z-less stratification up to z/L ∼ 1 in general (e.g., Basu et al, 2006;Yagüe et al, 2006;Mahrt, 2008). That is, as z/L increases, σ u /u * , σ w /u * , σ T /T * are nearly constant if z-less turbulence is valid (Nieuwstadt, 1984;Dias et al, 1995;Grachev et al, 2005;Basu et al, 2006;Hong , 2010).…”
Section: Resultsmentioning
confidence: 97%
“…This Fig. 7 shows that there are certain atmospheric situations (coinciding with those more stably-stratified) in which the model is unable to represent their corresponding scaling exponents (for example those situations present in the 14-15 night, where very strong stable stratification was observed - Yagüe et al, 2006 -), due to the fact that the scaling exponents are too high (for orders higher than 3) or too low (for orders lower than 3) for the model. Moreover, the minimum values (for orders lower than 3) or maximum values (for orders higher than 3) of the scaling exponents that the model is able to reproduce are very similar for different q values (see Fig.…”
Section: Data and Empirical Resultsmentioning
confidence: 99%